2017
DOI: 10.1371/journal.pone.0176000
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human explant derived cardiac stem cells from cryopreserved heart tissue

Abstract: The value of preserving high quality bio specimens for fundamental research is significant as linking cellular and molecular changes to clinical and epidemiological data has fueled many recent advances in medicine. Unfortunately, storage of traditional biospecimens is limited to fixed samples or isolated genetic material. Here, we report the effect of cryopreservation of routine myocardial biopsies on explant derived cardiac stem cell (EDC) culture outcomes. We demonstrate that immediate cryopreservation or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Finally, panning through ventricular lysate failed to demonstrate meaningful persistence of transplanted cells. Previous work has shown that long-term persistence of transplanted cells is very modest (1-2% of the initial injectate) 19, 20, 22, 23, 50. It is possible the number of cells remaining was below the detection threshold for the male-specific target used 28 but this result needs to be verified and future work to define the critical retention window leading to cell treatment effects needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, panning through ventricular lysate failed to demonstrate meaningful persistence of transplanted cells. Previous work has shown that long-term persistence of transplanted cells is very modest (1-2% of the initial injectate) 19, 20, 22, 23, 50. It is possible the number of cells remaining was below the detection threshold for the male-specific target used 28 but this result needs to be verified and future work to define the critical retention window leading to cell treatment effects needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of cell types, such as cardiomyocytes, endothelial cells, smooth muscle cells and cardiac resident stromal cells (CRSCs), such as fibroblasts and stem/progenitor cells, are found in the adult heart [1,2]. CRSCs have been isolated and characterized by the ex vivo culture of cardiac explants [3,4,5]. The conditioned media from cultured CRSCs exhibits cardioprotective and regenerative capabilities, being able to drive proliferation, cardiac differentiation and tube formation in endothelial cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, stem cells usage has been known as an attractive method, which could regenerate and repair the lost heart organ [6]. Nowadays, broadly used cells in the animal modeling are modeling that are somatic stem cells from various adult tissues, embryonic stem (ES) cells, and induced pluripotent stem (iPS) cells [7,8]. As mentioned earlier, somatic stem cells-derived from various tissues such as adipose tissue, bone marrow (BM), and heart have been used to regenerate dead myocardium; however, its efficiency is low due to progressive loss of functional role and reduced output [9].…”
Section: Introductionmentioning
confidence: 99%